2011
DOI: 10.1371/journal.pone.0027016
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Behavior and Depression in Smoking Cessation Treatments

Abstract: BackgroundTwo treatments for smoking cessation—varenicline and bupropion—carry Boxed Warnings from the U.S. Food and Drug Administration (FDA) about suicidal/self-injurious behavior and depression. However, some epidemiological studies report an increased risk in smoking or smoking cessation independent of treatment, and differences between drugs are unknown.MethodologyFrom the FDA's Adverse Event Reporting System (AERS) database from 1998 through September 2010 we selected domestic, serious case reports for v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
111
1
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(120 citation statements)
references
References 24 publications
6
111
1
2
Order By: Relevance
“…However, smoking relapse rates remain high even with varenicline treatment (McNeil et al, 2010;Raupach and van Schayck, 2011). In addition, varenicline is not without side effects, including nausea and serious psychiatric problems (Jorenby et al, 2006;Moore et al, 2011;Williams et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, smoking relapse rates remain high even with varenicline treatment (McNeil et al, 2010;Raupach and van Schayck, 2011). In addition, varenicline is not without side effects, including nausea and serious psychiatric problems (Jorenby et al, 2006;Moore et al, 2011;Williams et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the UK Medicines and Healthcare Products Regulatory Agency (MHRA) Yellow Card reports state that varenicline had the highest reported rate of depression disorders, and the secondhighest rate of non-fatal suicidal behaviour compared with other drugs in the MHRA study [55]. Similarly, Moore and colleagues studied the FDA's Adverse Event Reporting System (AERS) database from 1998 to September 2010 and found that varenicline substantially increased the risk of reported depression and suicidal/self-injurious behaviour [27].…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine in cigarettes is an addictive drug, and nicotine withdrawal produces a wide range of withdrawal symptoms such as headaches, nausea, anxiety, and depression. Previous smoking cessation studies have reported similar symptoms among smokers treated with bupropion, as well as with other nicotine replacement therapies [20,27].…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Moore et al assert that varenicline use is associated with an increased risk of suicidal/self-injury behavior and depression in smokers attempting to quit. 5 Data for this study were drawn from case reports of adverse drug events received by the FDA from 1998 to 2010. The authors identified 3,249 cases of suicidal behavior and depression, with varenicline accounting for 90% of reports.…”
mentioning
confidence: 99%